An Integrated approach of ethics and professional issues into engeneering curriculum. - Hrairi, Meftah; Khalifa, Othman Omran (IIUM Press, 2009)
The most common method used in the majority of higher education institutions remain to teach ethic as a standalone course. However, the courses currently offered appear insufficient to provide the students with the necessary ethics education needed by a practicing engineer. Hence, the need for some additional education in engineering ethics is a logical and obvious solution. There are two dilemmas to be faced: how to fit this into the curriculum, and how to make what it teaches into a routine part engineering? One way of answering these two questions is to teach engineering ethics in a way that brings home how integral it is to engineering work and avoid the addition of new ethics courses. If engineering ethics pervade the curriculum, then ethics will become a routine part of what engineerini students have to think about. In this paper, an integration approach of ethics and professional issue into some engineering courses is proposed.